HUBUNGAN BEBAN KERJA PERAWAT DENGAN KEPATUHAN PELAKSANAAN VENTILATOR ASSOCIATED PNEUMONIA (VAP) BUNDLE DI RUANG RAWAT INTENSIF - Syifa Putri Salsabila, (2022)
Patients in the intensive care unit are high-risk populations for nosocomial infections or Healthcare Associated Infections (HAIS). The latest data shows the number of HAIs changes, an increase of 35% in the case of Ventilator-Associated Pneumonia (VAP). Problems caused by VAP in critical patients are the time to extend treatment to increase the cost of treatment and the risk of death increases. The incidence of VAP in the intensive care unit can be minimized with a bundle of VAP. The success of the bundle VAP can be achieved one of them is by compliance in carrying out maintenance. The nursing profession tends to have a high workload and excessive workload can produce bad effects on patient care. The purpose of this study is to determine the relationship of the nurse's workload with the compliance of the implementation of the Bundle VAP in the intensive care unit. This research design uses a quantitative approach with cross-sectional designs. The sampling technique uses a total sampling with a total sample of 38 intensive room nurses. The results of Chi Square's analysis showed that there was a significant relationship between the workload of the nurse and the compliance with the implementation of the Bundle VAP in the intensive care unit (P-value = 0,000 < 0.05) (OR = 67.50; CI 95%). Hospitals are expected to conduct VAP prevention training, provide education for managing workloads, and create a strong teamwork culture.